Математичні моделі гістерезису - Лутчин, Микола Миколайович (НТУ "ХПІ", 2016)
В даній статті розглянуті способи представлення явища гістерезису. Використання гістерезису спостерігається в електротехніці, біології, гідрології, економіці, філософії та соціології. Моделювання здійснюється з урахуванням особливостей вхідних даних та необхідної точності розрахунків. Показані переваги та недоліки моделей Маделунга, Джона Чана, Джилса-Атертона, Прейзаха, Релея та графоаналітичний. Рекомендується для підвищення точності моделювання використовувати комбіновані методи або виконувати їх модифікацію з урахуванням особливостей представлення гістерезису.

In the paper, models of hysteresis are presented. Modeling is carried out with a specific of initial data and in accordance with the accuracy of calculations. Preisach model is highly accurate description of the process, but requires a large number of input parameters. Models of John Chan and Jiles-Atherton have highly simple calculations. They enable to simulate a real process conditions for a match characteristics. Rayleigh model provides accurate results in initial magnetization. This model recommended for use in the calculation of the steady state. Semigraphical methods give only an idea of the progress of hysteresis effects. It is recommended to improve the accuracy of modeling to use combined methods or to perform its modification allowing for the representing of specific features of hysteresis.
Mathematical models histeresys
Keywords: часткові петлі; крива намагнічування; модель Маделунга; модель Джона Чана; модель Джилса-Атертона; модель Прейзаха; Madelung model; John Chan model; Jiles-Atherton model